Aging interventions and therapies - Rattan, Suresh I. S. (World Scientific, 2005)
This comprehensive volume surveys the molecular, cellular, hormonal, nutritional, medical, and lifestyle strategies being tested and applied for the prevention, intervention, and treatment of age-related diseases. With authoritative contributions not just from researchers in academic institutions and pharmaceutical and cosmeceutical industries, but also practicing clinicians of both mainstream and alternative medicine, demographers and bioethicists, this book provides unique scientific, ethical, and social perspectives on the discussion of aging intervention. In addition, the latest technologies in development, which will have serious bearings on future aging interventions, are reviewed. "Aging Interventions and Therapies" is ideal for graduates and undergraduates in universities and medical and nursing colleges, as well as post-graduates researching different aspects of aging and anti-aging. The topics covered are also highly relevant for professionals in the pharmaceutical, cosmeceutical, nutrition and healthcare industries, and practicing clinicians looking for a reliable and up-to-date resource on aging intervention and therapy.